A Research Study Concerning the Regulatory Role of Organizational Justice in the Impact of Job Satisfaction on Organizational Commitment - Yazıcı, Ayşe Meriç; Güney, Salih; Uğurlu, Erginbay (Melih Topaloğlu, 2023)
Purpose- The study aims to reveal the regulatory role of organizational justice in the effect of job satisfaction on organizational commitment. Design/methodology/approach- The research sample consists of companies from the packaging sector in Halkalı and Silivri districts of Istanbul. The survey data were collected from 437 participants according to the five-point Likert scale and analysed by SPSS 22 and AMOS 24. Findings- When the effect of independent variables on organizational commitment was examined, it was seen that all variables had a significant effect on organizational commitment. The model established for the regulatory role of organizational justice perception in the relationship between organizational commitment and its sub-dimensions and job satisfaction was found to be significant. Discussion- The difference between the effectiveness of the dimensions of organizational justice on various aspects of job satisfaction and organizational commitment reveals that the results of this research are strong. The findings and information obtained will be useful for managers to improve their work with a sense of organizational justice. As a result, in this research, the regulatory role of organizational justice in the effect of job satisfaction on organizational commitment of employees in the packaging sector was tried to be determined. In this context, this research offers suggestions for managers and future studies.
Keywords: Job satisfaction; Organizational commitment; Organizational justice